Ambitions et limites du grand projet chinois des Nouvelles Routes de la soie - Emmanuel Lincot (Cahiers d’histoire.)
The interconnection between the two extreme poles of Eurasia is not a new idea per se. What is more original is to understand China's proposal to project beyond its borders in the aim to deploy a very extensive network both in economic and security fields is a worldwide and massive global strategy for the future. So much so that it would be wrong to confront the « New Silk Roads » project against the pro-American « Indo-Pacific » with a bipolar interpretation of the international relations. Because the project as defined by Xi Jinping concerns land and sea as well. It covers very diverse meanings; the latter are not necessarily compatible with a certain vision of Eurasianism as defended by the Russians, the Turks, or the Kazakhstanis.